Bridging Legal Pluralism Through Community-Based Islamic Education: Enhancing Sharia Literacy on Cryptocurrency and NFTs in Indonesia - Alqodr, Muhammad Farid Romadhoni; Awaluddin, Ayub; Rohmani, Annas Fajar; Al Farisi, Muhammad Salman (Universitas Muhammadiyah Surakarta, 2025)
The rapid development of digital finance has led to widespread adoption of cryptocurrency and Non-Fungible Tokens (NFTs), including among Indonesian Muslims. However, a gap remains between state policy and Islamic legal perspectives on the legitimacy of these digital assets. While the Indonesian government recognizes cryptocurrency as a tradable commodity, Islamic authorities such as the Indonesian Ulema Council (MUI) consider it haram due to elements of gharar (uncertainty) and maysir (gambling). This normative divergence, coupled with the absence of integrated sharia-based digital education, creates confusion and increases the risk of speculative or unethical practices. This study adopts a descriptive qualitative approach through library research, drawing on academic literature, state regulations, fatwas, and digital media content. The findings reveal that community-based Islamic education—rooted in platforms such as pesantren, majelis taklim, and digital Muslim communities—plays a strategic role in enhancing sharia literacy. Digital educational media like YouTube, podcasts, and e-learning serve as powerful tools for contextualizing Islamic teachings in the digital economy. Collaborative educational initiatives involving scholars, educators, and influencers have shown positive outcomes in building awareness and ethical understanding of digital financial instruments. This research suggests that integrating fintech content into Islamic educational curricula and empowering da'i and PAI teachers with digital literacy skills are essential to developing an ethically grounded and technologically literate Muslim society.